Timur-sultan and Kerim-birdi: Two attacks on Venetian Tana in 1410 and in 1418 - Karpov S.P. (Золотоордынское обозрение)
The purpose of the study is to consider the problem of the existence of the Venetian and Genoese trading stations in Tana within the territory of the Golden Horde city of Azak during the internecine war in the Golden Horde between the sons of Toktamysh and Idegei. Through an analysis of sources, an effort is made to determine the circumstances of the attacks of the Golden Horde khans and the level of damage that arose from them. Research materials: Unpublished documents of the State Archives of Venice (Italy), as well as Venetian chronicles and historical works of the 15th–16th centuries. Results and scientific uniqueness: The study of Venetian sources showed that during the second period of turmoil in the Golden Horde which erupted after the defeat of Toktamysh by Tamerlane, Tana trading stations underwent extremely difficult times during the period of the domination of beklerbek Idegei. The point of disagreement between the Tatar khans and the Venetians was the non-payment of a tax for renting land, called terraticum, by the Venetian merchants who traded at the mouth of the Don. The Venetians tried to maneuver between the sons of Toktamysh and the henchmen of Idegei, but since power in the Horde often changed hands at the time, Tana became a hostage in this internecine struggle. In 1410, Tana suffered from an unexpected night raid by Timur Khan and was captured. The damage amounted to between 100,000 and 120,000 ducats. Many Venetian sources tell us about these events, but with great discrepancies in details. Thanks to the inclusion of an important commerce-related source – the protocol of the Venetian judges on petitions – we can determine the exact date of the attack, the name of the khan, and the amount of damage. In 1418, there was an even more devastating second attack on Tana by Khan Kerim-birdi. After that, the Venetian Senate, having comprehensively studied the situation, decided to surround Tana with stone walls and repair its fortifications. Thanks to the erection of strong fortifications at Tana, it was possible for the town to hold out until the Ottoman Turkish conquest in 1475.